(untitled) (Contemporary Journal of Social Science Review, 2025)
Unemployment remains one of the most pressing socioeconomic challenges in Pakistan and has increasingly been linked to rising crime rates across the country. Persistent joblessness, particularly among youth, generates economic deprivation, social frustration, and psychological stress, which may compel individuals to engage in criminal activities as alternative means of survival. Grounded in Robert K. Merton’s Strain Theory, this study quantitatively examines the impact of unemployment on the rising crime rate in Pakistan, emphasizing how blocked access to legitimate economic opportunities produces strain that manifests in deviant behavior. Using a quantitative research design, the study analyzes empirical data to assess the relationship between unemployment levels and various forms of crime, including property and violent offenses. Statistical techniques are employed to determine the strength and significance of this relationship within the Pakistani context. The findings reveal a positive and statistically significant association between unemployment and crime, supporting the core propositions of Strain Theory that economic strain and unmet societal expectations increase the likelihood of criminal involvement. The study contributes to criminological literature by providing empirical evidence from Pakistan, a context that remains underrepresented in quantitative strain-based research. Policy implications highlight the need for employment generation, skill development, and social welfare interventions to reduce economic strain and mitigate crime. By addressing unemployment as a structural cause of crime, the study offers valuable insights for policymakers, law enforcement agencies, and social planners seeking sustainable solutions to crime prevention in Pakistan.